Letter (copy) - Tewson, Vincent
1938-08-30 038-0122-001 Secretary's. HVT/FC/EK/1750. 30th August, 1938. PERSONAL. Mr. W. Roberts, M.P., Banks House, Low Row, Carlisle. Dear Roberts, Many thanks for your letter of the 29th instant. Miss McCleland had a word with me in regard to the suggestion you make and I informed her that I could not see the possibility of packing anything else in our already overcrowded programme. Let me, however, deal with the points you raise. Firstly, you suggest a concert in which our children from the Barnet Home might be reinforced with some from the North of England. I am afraid this is quite impracticable as the fares and maintenance of the children in Blackpool would be an expensive item. The children at the Barnet Home are at the present time rehearsing a new programme and I know that matters are not yet at a stage when we would allow a public show to be given. I am afraid that one of the best Committees in the world, such as the Blackpool Committee, might be, could not make satisfactory arrangements at three or four days notice. In regard to your second paragraph, the General Council's Report contains a paragraph concerning Basque children. This Report is not on public sale 292/946/38/122(I)